Density, Temperature, and Comingled Species Affect Fitness within Carrion Communities: Coexistence in Phormia regina and Lucilia sericata (Diptera: Calliphoridae) - Patricia Okpara; Sherah VanLaerhoven (Insects, 2023)
Blow fly (Diptera: Calliphoridae) interactions vary between competition and facilitation. Female blow flies engage in aggregated egg-laying, resulting in larval feeding masses differing in density and species composition. Numerous species are abundant within the same season, and some oviposit near or directly on eggs of other species, modifying their oviposition location choice depending on the presence or absence of other species. The ability to coexist on carrion, a temporary resource, was successfully attributed to resource, spatial, and temporal heterogeneity. Despite these broad categorizations, the specific mechanisms of coexistence within blow fly communities require further investigation. This study investigates variation in temperature and larval density as potential mechanisms of coexistence between two forensically important blow fly species: Lucilia sericata Meigen and Phormia regina Meigen (Diptera: Calliphoridae). Larval density, species ratio mix, and ambient temperature during development were manipulated in the presence of conspecifics and heterospecifics in the laboratory, and the fitness of each species was measured. In heterospecific treatments, the survival and body size of P. regina increased even at high ambient temperatures. In contrast, the survival of L. sericata remained unaffected by density or presence of heterospecifics, whereas body size increased in L. sericata-dominated heterospecific treatments depending on temperature and density. The negative effects of density were observed at high ambient temperatures, suggesting that density impacts are a function of ambient temperature. Overall, species coexistence was dependent on temperature, which mediated the outcome of species interactions.